1982
DOI: 10.1152/ajpendo.1982.242.2.e87
|View full text |Cite
|
Sign up to set email alerts
|

Arginine metabolism and urea synthesis in cultured rat skeletal muscle cells

Abstract: Skeletal muscle is known to contain arginase, but, because this enzyme is also present in erythrocytes, the exact origin of arginine-derived ornithine in peripheral tissues is uncertain. In the present studies, skeletal muscle cells obtained from regenerating hindlimb muscle of adult rats were grown in primary tissue culture for approximately 3 wk and then studied in regard to changes in medium amino acid concentrations over a 48-h period. The consumption of arginine and serine was observed in parallel with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Spermidine can then be used for eIF5A hypusination. Rat skeletal muscle cells in culture possess high arginase activity (Pardridge et al, 1982). So, the treatment of satellite cells with L-arginine could suppress the cell differentiation inhibitory effect of GC7.…”
Section: Journal Of Cellular Physiology S K E L E T a L M U S C L E Smentioning
confidence: 99%
“…Spermidine can then be used for eIF5A hypusination. Rat skeletal muscle cells in culture possess high arginase activity (Pardridge et al, 1982). So, the treatment of satellite cells with L-arginine could suppress the cell differentiation inhibitory effect of GC7.…”
Section: Journal Of Cellular Physiology S K E L E T a L M U S C L E Smentioning
confidence: 99%
“…This makes serum a potential source of cyanate for the encysted worm. However, Pardridge et al (1982) demonstrated in culture, that rat striated muscle cells derived from regenerating hindlimbs were well capable of synthesizing ornithine and urea, and that production was linked to the utilization of serine and arginine in the presence of high levels of cell-derived arginase I which has been linked to a multitude of human diseases ( Caldwell et al, 2018 ). Pandya et al (2019) also reported elevated levels of arginase I in aged muscle cells as did Wu et al (2001) who linked arginase I levels in rat aortic smooth muscle cells to the escalation of cell proliferation.…”
Section: Sources Of Host-derived Cyanatementioning
confidence: 99%
“…Serum arginine levels were significantly reduced in both AG-and UAG-treated mice ( Figure 4E), whereas serum taurine and threonine levels were significantly reduced in AG-treated mice only ( Figures 4F and 4G). Skeletal muscle is known to express arginase (52). Although the major sites of arginine biosynthesis are the small intestines and kidney, the enzyme arginase drives l-arginine catabolism to l-ornithine, in competition with catabolism to nitric oxide (NO) by NO synthase; this competition has been suggested to limit NO production (53).…”
Section: Ag and Uag Treatment Protected Against Fast-induced Muscle Amentioning
confidence: 99%